Fixed field alternating gradient accelerators - Sheehy, S (CERN, 2017)
These notes provide an overview of Fixed-Field Alternating-Gradient (FFAG) accelerators for medical applications. We begin with a review of the basic principles of this type of accelerator, including the scaling and non-scaling types, highlighting beam dynamics issues that are of relevance to hadron accelerators. The potential of FFAG accelerators in the field of hadron therapy is discussed in detail, including an overview of existing medical FFAG designs. The options for FFAG treatment gantries are also considered.